Hepatitis C virus among childbearing women in Scotland: prevalence, deprivation, and diagnosis. Issue 4 (11th March 2004) - Hutchinson, S J; Goldberg, D J; King, M; Cameron, S O; Shaw, L E; Brown, A; MacKenzie, J; Wilson, K; MacDonald, L
Abstract : Objectives: (A) To examine the prevalence and demographic characteristics of hepatitis C virus (HCV) infection among childbearing women in Scotland; and (B) to determine the extent of maternal HCV infection diagnosed prior to birth. Methods: (A) Residual dried blood spot samples from routine neonatal screening, collected throughout Scotland during March-October 2000, were unlinked from identifiers and tested anonymously for HCV antibodies; and (B) electronic record linkage of Scotland's databases of births and diagnosed HCV infections was performed. Results: (A) Of 30 259 samples, 121 were enzyme linked immunosorbent assay repeat reactive and 88 of these were confirmed as anti-HCV positive in the recombinant immunoblot assay, representing a seroprevalence of 0.29–0.40%. HCV seroprevalence was high among 25–29 year olds (0.4–0.57%), in high deprivation areas (0.92–1.07%), and in Greater Glasgow (0.83–0.96%) and Grampian (0.38–0.62%). Adjusted relative risk for HCV infection was highest among residents in high deprivation areas of Glasgow (7.2 (95% confidence interval 2.0–25.5)). (B) Of 121 HCV infections found among women at delivery, 24% and 46% were estimated to have been diagnosed prior to pregnancy and birth, respectively. Conclusions: HCV prevalence among Scottish childbearing women is consistent with that expected from injecting drug use. Based on reported rates of mother to child transmission, 8–11 paediatric infections are expected per annum. Diagnosis in only 24% of infected women prior to pregnancy indicates the extent to which HCV goes unrecognised in the injecting community. The current HCV screening approach—to test only those with a history of injecting drug use (or other risk factors for infection)—identifies approximately a quarter of previously undetected infections among pregnant women.